Analysing rock mass response to undercutting using real time MPBX data - Batkhuu, B; Smith, R; Batgerel, A; Mardiansyah, F; Moorcroft, T (MassMin 2024: Proceedings of the 9th International Conference & Exhibition on Mass Mining, 2024)
It is widely acknowledged that undercutting is imperative to the success of a block cave. At Oyu Tolgoi, significant investment has been made in geotechnical instrumentation to facilitate understanding of the response of moderate to highly fractured rock mass to undercutting in a deep, high-stress environment. Approximately 488 multi-point borehole extensometers (MPBX) have been installed in Oyu Tolgoi Panel 0 footprint. Individual MPBX readings are fed into an integrated live data management platform, enabling real-time geotechnical assessments. These assessments provide insight into rock mass response to undercutting within various geotechnical and geological environments. The comprehensive instrumentation network facilitates proactive monitoring of ground conditions, which not only mitigates safety risks but also reduces production delays through scheduled rehabilitation. In addition to operational benefits, the data is used for back analysis, calibration of numerical modelling and validation of cave management rules.